2017
DOI: 10.1097/ajp.0000000000000396
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Neck Pain, Low Back Pain, and Knee Pain and Their Related Factors in Community-Dwelling Adults in Iran

Abstract: This is the first study investigating the prevalence of CNP, CLBP, and CKP in the national population of Iran. It shows some modifiable risk factors for CMP, and suggests that affordable planning for these risk factors can be valuable in preventing CMP globally. However, this is a cross-sectional study and future longitudinal studies in this field are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 47 publications
4
72
1
1
Order By: Relevance
“…Mean pain level of patient with chronic knee pain in Nepali version of Numerical Pain Rating scale was 5 with maximum NPRS score7 and minimum score of 2.0. The main cause of chronic knee pain in following study shows knee osteoarthritis which is consistent with the similar study that has been done in Iran [5].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mean pain level of patient with chronic knee pain in Nepali version of Numerical Pain Rating scale was 5 with maximum NPRS score7 and minimum score of 2.0. The main cause of chronic knee pain in following study shows knee osteoarthritis which is consistent with the similar study that has been done in Iran [5].…”
Section: Discussionsupporting
confidence: 90%
“…In a study done in the community dwelling adults of Iran, the prevalence of chronic knee pain was found to be 29.97% [5].Chronic knee pain is commonly due to arthritic change and knee osteoarthritis is one of the leading cause of chronic knee pain [6]. The patellofemoral pain syndrome is one of the leading causes of pain in adults and adolescents [7].Since knee is one of the largest weight bearing joint in our body, it is always prone to overload and overuse causing pain and limiting the lower limb function [8].…”
Section: Introductionmentioning
confidence: 99%
“…This research had the endorsement of the institutional ethics committee; all of the participating subjects signed the informed consent form 18,19 .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“… 17 Another national cross-sectional study from the US shows that physical activity (even at low levels), tobacco use, alcohol intake, sleep quality, and BMI are all associated with LBP. 18 Similarly, studies conducted at a national level in Iran 19 and Canada 20 on LBP, and in Spain on NP, 21 suggest the importance of lifestyle behavior. However, longitudinal studies have shown either weak or nonsignificant associations.…”
Section: Introductionmentioning
confidence: 97%